Risk Factors Associated with the Prevalence of Antibodies Against Brucellosis in Equids from Western Pará, Brazil - Eloine Maria Bandeira Picanço; Francisco Flávio Vieira de Assis; Poliana Leão Peleja; Ana Beatriz Barbosa de Sousa; Raimundo Alves Barrêto Júnior; Ronaldo Francisco de Lima; Kedson Alessandri Lobo Neves; Antonio Humberto Hamad Minervino (Microorganisms, 2025)
This study aimed to determine the prevalence of antibodies against equine brucellosis in three distinct equid groups (farm animal, urban carthorse, and sport horse) in Western Pará, Brazil, and to identify associated risk factors. A cross-sectional study, involving 75 farms across 14 municipalities, sampled 1069 equids composed of urban carthorses and sport horses. Serum samples were tested for antibodies against Brucella spp. using the buffered acidified plate antigen (BAPA) test for screening, followed by the serum agglutination in tubes with 2-mercaptoethanol (2-ME) for confirmation. Univariate and multivariate analyses assessed associations between brucellosis and potential risk factors. Out of the 1059 equids sampled, 4.05% (95% CI: 3–5.5%) tested positive in the BAPA test. Of the 44 BAPA-positive samples, 11 were confirmed positive by 2-ME, 15 were inconclusive, and 18 were negative, yielding an animal-level prevalence of 1.03% (95% CI: 0.5–1.8%) for equine brucellosis in western Pará. Prevalence was higher in the Southwest Pará Mesoregion (p = 0.047) compared to the Lower Amazon Mesoregion. No significant associations were found with animal type, reproductive problems, animal sex, species, breed, and age group. Out of the 75 farms, 8 (10.66%) had at least one seropositive equid. Confirmed cases were identified in five municipalities (Brasil Novo, Uruará, Altamira, Rurópolis, and Itaituba). This first report of equine brucellosis in Western Pará underscores the need for enhanced surveillance and control measures to mitigate its zoonotic risk to humans and transmission to other animals.